The Impediment Factors of Customers Intentions to Borrow in Peer to Peer Lending Apps - Khairul Ikhsan; Nurhayani Nurhayani (University of Merdeka Malang, 2023)
In the last decade, Indonesia's fintech trend are supported by the growth of Internet users. A recent report by OJK in 2021 shows that online loan services continue to increase by the millennial generation's dominance. It's because online loan services are easier to gain rather than conventional loan services. Unfortunately, its service provides several potential threats to its users. Moreover, religious values play a critical role in shaping consumers' attitudes and behavior towards products or services. The purpose of this study is to analyze the role of perceived risk: security risks and privacy risks, and religiosity in predicting customers' intention to borrow in P2P Lending apps. The research approach is quantitative, with a random sampling technique, and the research sample is 86 respondents. The data were analyzed by using multiple linear regression with IBM SPSS 23. Based on the study results, it can be concluded that security risk has a negative and significant effect in predicting the intention to borrow in P2P Lending apps, but no relationship between privacy risk and religiosity on the intention to borrow. As a managerial implication, our findings can help the company to focus on providing highly secure apps and promoting and campaigning the confidentiality of users' personal information.